Predicting Transaction Numbers İn Atm - Karasu, Ahsen Ceren (MEF Üniversitesi, Fen Bilimleri Enstitüsü, 2018)
ATMs continue to be one of the most important channels for banks to touch their customers. They play an active role in life in terms of cash access and banking experience. The ability of a bank to predict the number of transactions that will occur from ATMs is crucial for the proper control of the budgetary source. When cash is loaded into ATMs, the average transaction made from that ATM is taken into consideration and alarm mechanisms can be activated when a decreasing trend is observed on transaction basis.Before a new ATM is set up, the banks investigate how often customers in that area use other bank ATMs and calculate the commission costs incurred from those uses. As a result, the number of transactions made from ATMs is one of the most monitored KPIs of a bank and has important place in the cash management of the bank.The aim of this study is to estimate the number of future transactions with Auto Regressive Moving Average (ARIMA) method based on the number of transactions that occurred from ATMs.

ATM’ler bankalar için müşterilerine dokunabildikleri en önemli kanallardan biri olma görevini sürdürmektedir. Nakite ulaşma ve bankacılık deneyimini yaşamada etkin rol oynarlar.Bir bankanın ATM'lerden yapılan işlem sayısını tahmin etme yeteneği, bütçe kaynağının uygun şekilde kontrolü için çok önemlidir. ATM'lere nakit ikmal edildiğinde söz konusu ATM'den yapılan ortalama işlem dikkate alınır ve işlem bazında azalan bir eğilim gözlendiğinde alarm mekanizmaları etkinleştirilebilir. Yeni bir ATM kurulmadan önce, bankalar o lokasyondaki müşterilerinin diğer banka ATM'lerini ne sıklıkla kullandığını ve bu kullanımlardan kaynaklanan komisyon masraflarını hesaplar. Sonuç olarak, ATM'lerden yapılan işlem sayısı, bir bankanın en çok izlenen KPI'larından biridir ve bankanın nakit yönetiminde önemli bir yere sahiptir. Bu çalışmanın amacı, ATM'lerden kaynaklanan işlem sayısına dayanarak gelecekteki işlem sayısını oto regresif hareketli ortalama (ARIMA) ile tahmin etmektir.
ATM işlem tahminleme
Keywords: Transaction; Regression; ARIMA; Prediction; Time Series; Exploratory Data Analysis; Regresyon; Tahminleme; Zaman Serileri; Data Analizi